2021
DOI: 10.1016/j.crad.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transarterial embolisation in patients with life-threatening spontaneous retroperitoneal haematoma

Abstract: To evaluate the technical and clinical success of embolisation in patients with lifethreatening spontaneous retroperitoneal haematoma (SRH) and to assess predictors of clinical outcome.MATERIALS AND METHODS: Thirty patients (mean age: 71.9AE9.8 years) with SRH underwent digital subtraction angiography (DSA). All patients received anticoagulant or antiplatelet medication or a combination of both at the time the SRH occurred.RESULTS: Pre-interventional computed tomography angiography (CTA) revealed active retrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
2
13

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(58 citation statements)
references
References 29 publications
11
32
2
13
Order By: Relevance
“…There are now retrospective studies suggesting the advantages of liquid embolic agents as they provide rapid complete occlusion compared to others such as coils. [12] In the study, most of the embolization were performed with Onyx-18 (Table 2). The selection of this material was mainly based on two factors, on the one hand the morphology of the responsible artery, in all cases small calibre arteries, and on the other hand the presence of a coagulation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…There are now retrospective studies suggesting the advantages of liquid embolic agents as they provide rapid complete occlusion compared to others such as coils. [12] In the study, most of the embolization were performed with Onyx-18 (Table 2). The selection of this material was mainly based on two factors, on the one hand the morphology of the responsible artery, in all cases small calibre arteries, and on the other hand the presence of a coagulation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive treatments, such as surgery or transarterial embolization of the bleeding vessels, are currently reserved to patients with expanding hematomas, that are hemodynamically unstable or with neurological impairment (especially in posterior wall hematomas). In recent years, the endovascular treatment of AWH has been increasingly used for patients in which conservative treatments were not sufficiently effective, and it is often preferred to surgical interventions [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, AWH is a condition more commonly observed in elderly patients, especially those with comorbidities [ 18 ]. In a study conducted by Klausenitz et al [ 2 ] on 30 patients who underwent DSA and embolization therapy for retroperitoneal bleeding, the mean age of the patients was 71.9 ± 9.8 years; in a review of the literature on rectus sheath hematoma, Hatjipetrou et al [ 3 ] revealed a mean age of patients suffering from this condition ranging between 46 to 69 years. Moreover, a study performed by Barral et al [ 19 ] on 112 patients with spontaneous soft-tissue hematomas who underwent TAE revealed a mean age of 72 ± 14 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations